Direct synthesis of carbide-derived carbon monoliths with hierarchical pore design by hard-templating - Nickel, Winfried; Oschatz, Martin; Von Der Lehr, Martin; Leistner, Matthias; Hao, Guang-Ping; Adelhelm, Philipp; Mueller, Philipp; Smarsly, Bernd M.; Kaskel, Stefan (Journal of Materials Chemistry A, 2014)
Carbide-derived carbon Monoliths (CDC-Ms) containing a multimodal arrangement with high volumes of micro- meso- and macropores are prepared by direct nanocasting of silica monoliths with polycarbosilane precursors. CDC-Ms show well-defined pore structures along with specific surface areas of more than 2600 m2 g-1 and overall pore volumes as high as 3.14 cm3 g-1. They exhibit advanced gas filtration properties compared to purely microporous materials due to enhanced storage capacities and kinetics as demonstrated by thermal response measurements based on InfraSORP technology. © 2014 the Partner Organisations.
CRIS-Team Scopus Importer:2023-03-20